2004
DOI: 10.2337/diabetes.53.7.1890
|View full text |Cite
|
Sign up to set email alerts
|

A 212-kb Region on Chromosome 6q25 Containing the TAB2 Gene Is Associated With Susceptibility to Type 1 Diabetes

Abstract: The IDDM5 gene, which is identified by whole-genome searches, is located on chromosome 6q25. TAB2 (MAP3K7IP2 [mitogen-activating protein kinase kinase kinase 7 interacting protein 2]) is a potential candidate gene for type 1 diabetes because it is located on chromosome 6q25 and is involved in nuclear factor (NF)-B regulation. We have conducted familial association studies using 478 families and demonstrate that a type 1 diabetes susceptibility gene resides within a 212-kb region containing the TAB2 gene (Tsp ‫… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 23 publications
0
31
2
Order By: Relevance
“…For rs237025, results in each of the original studies indicated overtransmission of one of the two alleles to affected offspring but differed in the identity of the allele. The current study failed to confirm either of these positive findings despite having 80% power to detect the transmission rate of 56.6% reported by Owerbach et al 24 and more than 90% power to detect the transmission rate of 58.6% reported by Guo et al 18 The three studies differ methodologically in several areas, the statistical methods used to analyze the data, the selection of subjects, and the genotyping technologies, with one or more of these factors possibly relevant to discordant results obtained. The TDT is not a valid test of association when used in families with multiple affected siblings and the study by Owerbach et al, as well as the current study, employed alternative tests that can correctly account for data derived from such families.…”
Section: Resultscontrasting
confidence: 93%
See 4 more Smart Citations
“…For rs237025, results in each of the original studies indicated overtransmission of one of the two alleles to affected offspring but differed in the identity of the allele. The current study failed to confirm either of these positive findings despite having 80% power to detect the transmission rate of 56.6% reported by Owerbach et al 24 and more than 90% power to detect the transmission rate of 58.6% reported by Guo et al 18 The three studies differ methodologically in several areas, the statistical methods used to analyze the data, the selection of subjects, and the genotyping technologies, with one or more of these factors possibly relevant to discordant results obtained. The TDT is not a valid test of association when used in families with multiple affected siblings and the study by Owerbach et al, as well as the current study, employed alternative tests that can correctly account for data derived from such families.…”
Section: Resultscontrasting
confidence: 93%
“…31 In the current study, accuracy of the genotyping for the key SNP in the TAB2/SUMO4 region, rs237025, was assessed by genotyping a blinded resample of 10% of the subjects (272/2604) by an alternative method. This method, primer extension with detection by denaturing high-performance liquid chromatography, is the same as that employed by Owerbach et al 24 although the specific primer sequences used may differ.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations